Analysis of Students' Errors in Solving HOTs-Based Mathematics Problems Using The Newman Procedure - Nazla Salsa Billa; Sri Lestari Manurung (Program Studi Pendidikan Matematika Universitas Katolik Santo Agustinus Hippo, 2025)
One strategy to improve students' mathematical competence in education is to train them to use High Order Thinking Skill (HOTS)-type questions. HOTS is an expertise in the process of critical, reflective, metacognitive, logistical, and creative thinking possessed by students. Mistakes made by students in working on High Order Thinking Skill (HOTS) type math problems need to be analyzed; one that can be used is the Newman analysis procedure error. Therefore, this study aims to analyze students' errors in solving HOTS problems using the Newman procedure. This study uses a qualitative descriptive method. The subjects of the study were 59 students of SMA Negeri 7 Medan, class XI IPA. The researcher selected 6 students, comprising 2 high-category students, 2 medium-category students, and 2 low-category students. The data collection techniques used by the researcher were essay tests, interviews, and documentation. The results of the study obtained 4 types of errors, namely errors in understanding the problem (comprehension) made by students of 79.10%; transformation errors (transformation) made by students of 43.37%; process skill errors (process skill) made by students of 24.29%; and errors in writing the final answer (endcoding) made by students of 74.01%. Therefore, the most common errors made by students are errors in understanding the problem (comprehension), made by 79.10% of students. This study is expected to be useful for teachers to provide information about the location of student errors in working on HOTS-type math problems.